Generation Scotland – Transparency in the data access process - Campbell, Archie; Wood, Alex; Flaig, Robin; McCartney, Daniel; Whalley, Heather; Sudlow, Cathie (International Journal of Population Data Science, 2024)
Background Generation Scotland (GS) is large family-based cohort study established as a resource for research into the genetic and environmental determinants of physical and mental health. Participants completed a baseline questionnaire and clinic visit in 2006-2011. 24,084 Participants 5,501 Families NHS data linkage 22,402 (93%) Genotype array data 20,026 (83%) DNA methylation data 18,876 (78%) In 2019 funding was obtained to expand the existing GS cohort. By 2025 NextGenScot aims to: Recruit 20,000 new participants online Expand eligibility to 12-17 year olds Collect saliva samples by post for genotyping Linkage to NHS and other administrative data Details on how to join at www.gen.scot Participants consented to linkage to NHS Scotland medical records which offer longitudinal phenotype information. Linkage is conducted using the Community Health Index (CHI). Introduction GS receives 30-40 requests for access to data and/or samples every year, and has been included in over 380 publications. Research proposals are subject to review by the GS Access Committee. Details of the application process terms and conditions for access are available on the GS website, and now on the new research access website. The previous GS access process was based on an application form in Word, downloaded from the main GS website. We are replacing this with a new online research access system, adhering to transparency standards1, helped by HDR Alliance Transparency funding. After researchers publish their results, a link to the publication and a lay summary is currently posted on the GS website, with a spreadsheet listing papers. We will now make this information available and searchable for researchers, participants and the public on the new research access website. Methods We are developing a website, using in-house staff, with HDR Alliance Transparency contributing to their salaries. The system coding uses Django (a Python tool) linked to a MySQL database, a platform widely used for such projects, enabling faster development in a secure environment. Transparent access to GS data for registered users View summary of data available Query the summary data to see if it fits research requirements Select data requested from data dictionaries Get a detailed quote for access charges Complete application form showing the project complies with the Five Safes2 Upload supporting documentation (e.g. protocol, DPIA, ethics, etc) Track progress of their application review, approval and delivery Researchers will be required to submit a lay summary of their application GS participants, researchers and the public can view: List of approved applications with lay summaries Summaries of ongoing projects which will link to eventual publications Searchable list of publications Result The new system is undergoing internal testing, using data imported from previous and ongoing access requests (May 2024). We will then pilot it with selected external researchers and GS participants (June 2024), with a plan to launch it for public access in July/August 2024. The GS Access Committee and admin team will be able to streamline the review and approval process, giving an improved turnaround time. Conclusions We were already planning to develop a new online application system, but the Transparency grant funding has enabled us to extend the functionality beyond a simple form-filling system. The new access website will give researchers more information about the application process, the data and samples available, see what other research has been approved in their area of interest, and track the progress of their project from enquiry through to publication. By adding a participant/public access area, with lay summaries of projects and publications, GS participants will be able to see how their data is being used for public benefit, as can potential new volunteers or other interested parties. Notes The URL for the new website is www.gsaccess.org The main GS website is at www.generationscotland.org References Transparency Standards https://zenodo.org/record/8262453 Five Safes https://ukdataservice.ac.uk/help/secure-lab/what-is-the-five-safes-framework/